2022
DOI: 10.1007/s11916-022-01094-y
|View full text |Cite
|
Sign up to set email alerts
|

Headache After Vaccination: An Update on Recent Clinical Trials and Real-World Reporting

Abstract: Purpose of Review The aim of this review is to characterize headache as a vaccine adverse event (VAE) in clinical trials. Recent Findings Of the recent phase III vaccine RCTs (non-COVID-19), 53 studies reported on headache (13 infectious agents). The median rate (interquartile range) of headache was 15.6% ( IQR : 9.6–37.6%). Of these, 24.5% of the RCTs reported headache greater in the vaccine group compared to the placebo/control group. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 93 publications
(154 reference statements)
0
5
0
1
Order By: Relevance
“…Sixty‐two articles were identified (Appendix S4). According to the Vaccine Adverse Events Reporting System, headache was the fifth most reported AE post‐vaccination after administration of any SARS‐CoV‐2 vaccine [84]. Notably, headache is a frequent AE after any vaccination [85].…”
Section: Resultsmentioning
confidence: 99%
“…Sixty‐two articles were identified (Appendix S4). According to the Vaccine Adverse Events Reporting System, headache was the fifth most reported AE post‐vaccination after administration of any SARS‐CoV‐2 vaccine [84]. Notably, headache is a frequent AE after any vaccination [85].…”
Section: Resultsmentioning
confidence: 99%
“…31 Purported mechanisms of headache and new daily persistent headache developing after vaccination include systemic reactogenicity with the release of prostaglandins (such as those in the E family), interleukin-6, and C-reactive protein, increased blood-brain barrier permeability, and the activation of trigeminal nociceptors. 30,32 A stressful life event may be the second most frequently reported inciting factor in new daily persistent headache, ranging from 10% to 20% in many series. 10,11,17 As stress or stress let down (moving from high-stress to low-stress environments) can be a strong migraine trigger, and a major stressful life event can incite migraine to progress to chronic migraine, this observation for new daily persistent headache could suggest underlying migraine biology.…”
Section: Commentmentioning
confidence: 99%
“…29 Among non-COVID-19 vaccines, headache occurs most commonly after vaccination for varicella-zoster virus, followed by influenza and human papillomavirus. 30 However, it is important to note that in an analysis of the Vaccine Adverse Event Reporting System, the risk of experiencing headache is 500 times higher with COVID-19 infection relative to vaccination. 31 Purported mechanisms of headache and new daily persistent headache developing after vaccination include systemic reactogenicity with the release of prostaglandins (such as those in the E family), interleukin-6, and C-reactive protein, increased blood-brain barrier permeability, and the activation of trigeminal nociceptors.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Headache is also one of the most frequent symptoms reported after COVID-19 vaccines, described in 39-59% of patients in pivotal studies [ 8 - 10 ]. A recent systematic review of phase III vaccine randomized clinical trials not related to COVID-19 reported a median rate of headache of 15.6% –interquartile range (IQR): 9.6-37.6%–, a lower rate than the 39% (IQR: 28-50%) reported following COVID-19 related-vaccines [ 12 ]. In a study that evaluated 314,610 neurological adverse events reported to the United States Vaccine Adverse Events Reporting System, out of 306,907,697 COVID-19 vaccine doses administered, headache was the most frequently reported adverse effects [ 13 ].…”
Section: Introductionmentioning
confidence: 99%